Disseminated tuberculosis presenting as acute coronary syndrome. - Paul, GK; Bari, MS; Bari, MA; Debnath, RC; Majumder, RK; Chanda, SK; Siddique, SR; Khan, TA; Khan, MK (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):709-11 The abstract of this article is available on the PubMed website